2016
DOI: 10.2967/jnumed.115.166918
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tumor Uptake Heterogeneity Characterization Between Static and Parametric 18F-FDG PET Images in Non–Small Cell Lung Cancer

Abstract: 18 F-FDG PET is well established in the field of oncology for diagnosis and staging purposes and is increasingly being used to assess therapeutic response and prognosis. Many quantitative indices can be used to characterize tumors on 18 F-FDG PET images, such as SUV max , metabolically active tumor volume (MATV), total lesion glycolysis, and, more recently, the proposed intratumor uptake heterogeneity features. Although most PET data considered within this context concern the analysis of activity distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
(57 reference statements)
3
34
0
1
Order By: Relevance
“…It has also been shown that the use of a respiration-averaged CT scan instead of a helical CT scan for attenuation correction of the PET data has a greater effect on SUV and total lesion glycolysis than on TA metrics [83]. Another study demonstrated that TA features calculated in parametric maps derived from dynamic PET acquisitions or from corresponding static SUV images are not significantly different, suggesting that heterogeneity quantification on parametric images using TA may not provide significant additional information compared to that provided by static SUV images [84]. Finally, it has also been shown that even basic stochastic effects of PET acquisitions can affect some TA metrics [85].…”
Section: Repeatability and Reproducibility/robustnessmentioning
confidence: 99%
“…It has also been shown that the use of a respiration-averaged CT scan instead of a helical CT scan for attenuation correction of the PET data has a greater effect on SUV and total lesion glycolysis than on TA metrics [83]. Another study demonstrated that TA features calculated in parametric maps derived from dynamic PET acquisitions or from corresponding static SUV images are not significantly different, suggesting that heterogeneity quantification on parametric images using TA may not provide significant additional information compared to that provided by static SUV images [84]. Finally, it has also been shown that even basic stochastic effects of PET acquisitions can affect some TA metrics [85].…”
Section: Repeatability and Reproducibility/robustnessmentioning
confidence: 99%
“…The quantitative metrics evaluated in this study were MATV, SUV max , SUV mean , total lesion glycolysis (TLG), and several textural intratumor heterogeneity features. These features included a global heterogeneity indicator (i.e., area under the curve of the cumulative intensity histogram, CIH AUC ) (16), and some local heterogeneity features, such as homogeneity, entropy, dissimilarity, high-intensity emphasis (HIE), and zone percentage (ZP). These features were selected because of their reproducibility and robustness (8,16,17).…”
Section: Quantitative Uptake Metricsmentioning
confidence: 99%
“…These features included a global heterogeneity indicator (i.e., area under the curve of the cumulative intensity histogram, CIH AUC ) (16), and some local heterogeneity features, such as homogeneity, entropy, dissimilarity, high-intensity emphasis (HIE), and zone percentage (ZP). These features were selected because of their reproducibility and robustness (8,16,17). MATV, SUV max , SUV mean , TLG, and CIH AUC were calculated with in-house software, whereas local heterogeneity features were obtained with the Pyradiomics package (18).…”
Section: Quantitative Uptake Metricsmentioning
confidence: 99%
“…The dynamic course of the 18 F-FDG spatial distribution in the targeted tissues may reveal highly useful clinical information on tissue's metabolic properties, such as the metabolic rate of glucose uptake post 18 F-FDG injection. These image metrics could, in turn, facilitate tumor characterization and therapy response assessment [6][7][8][9]. For this reason, dynamic PET imaging techniques were also introduced allowing the scanning of a limited axial field-of-view (single bed position) over time to enable the extraction of important tracer kinetic parameters, such as the uptake rate.…”
Section: Introductionmentioning
confidence: 99%